Right Heart Catheterization Hemodynamic Parameters and Cardiovascular Adverse Events in Advanced Heart Failure: A Retrospective Cohort Study - Dian Yaniarti Hasanah; Jordan Budiono; Prisca Gisella Wibowo; Faiza Shafia; Hawani Sasmaya (The Indonesian Heart Association, 2026)
Background: Right Heart Catheterization (RHC) is an important tool in advanced heart failure because it provides invasive assessment of hemodynamics, congestion, pulmonary hypertension, and right ventricular function, and helps determine candidacy for advanced therapies. However, the prognostic value of RHC-derived hemodynamic parameters in real-world advanced heart failure remains unclear. This study aimed to describe the clinical, echocardiographic, and invasive hemodynamic characteristics of patients with advanced heart failure undergoing RHC and to explore their association with Cardiovascular Adverse Events (CVAE). Methods: This retrospective cohort study was conducted at two tertiary referral centers in Indonesia. Consecutive adult patients with advanced heart failure who underwent RHC were included. The primary outcome was CVAE, defined as a composite of cardiovascular death or rehospitalization due to acute heart failure, arrhythmia, or cardiogenic shock during a median follow-up of 6 (IQR 3-12) months after the index RHC. Baseline clinical, echocardiographic, and invasive hemodynamic data were collected from medical records and catheterization reports. No formal sample size calculation was performed. Patients with and without CVAE were compared, and bivariate logistic regression was used to explore associations between hemodynamic parameters and CVAE. Results: A total of 33 patients were included, and 22 (68.6%) developed CVAE. Mean age was 48.0 ± 11.3 years, and 29 patients (87.9%) were male. Most patients were INTERMACS profile 4, and 27 (81.8%) had combined post- and pre-capillary pulmonary hypertension. Compared with 11 patients without CVAE, the 22 patients with CVAE had lower cardiac output (3.23 ± 0.8 vs 3.99 ± 1.1 L/min; p=0.027), lower cardiac index (1.85 ± 0.4 vs 2.34 ± 0.7 L/min/m²; p=0.019), and lower pulmonary artery pulsatility index (0.56 [0.14-1.31] vs 1.35 [0.53-4.38]; p=0.044). Other hemodynamic parameters were not significantly different. In bivariate logistic regression, higher cardiac output, cardiac index, and pulmonary artery pulsatility index were associated with lower odds of CVAE. Conclusion: In this two-center retrospective cohort of patients with advanced heart failure undergoing RHC, lower cardiac output, lower cardiac index, and lower pulmonary artery pulsatility index were associated with CVAE, whereas conventional pressure-based and pulmonary vascular parameters were not. These findings suggest that impaired forward flow and reduced right ventricular-pulmonary arterial pulsatile reserve may be important for risk stratification in advanced heart failure.